Effect of fruit maturity on volatiles and sensory descriptors of four mandarin hybrids. Issue 5 (6th April 2020) - Hijaz, Faraj; Gmitter, Fred G.; Bai, Jinhe; Baldwin, Elizabeth; Biotteau, Alice; Leclair, Clotilde; McCollum, T. Greg; Plotto, Anne
Abstract : Abstract: Mandarins (or tangerines) are mainly consumed as fresh fruits due to the ease of peeling and desirable flavor. Sweetness, acidity, and flavor of mandarin are the most important criteria for consumer preference. The objective of this study was to evaluate the effects of harvest date on sensory and chemical components of four mandarin cultivars (Murcott, 411, Temple, and 'LB8‐9' Sugar Belle®). Volatiles were extracted from the headspace of juice samples with solid phase microextraction (SPME) and analyzed using gas chromatography‐mass spectrometry (GC‐MS). The optimum harvest window for eating quality of 411 was late January to mid‐February (soluble solids content [SSC]/titratable acidity [TA]: 11.3 to 14.0), Sugar Belle® fruits were best tasted when harvested from mid‐ to end of January (SSC/TA: 14.1 to 16.1), and February was the best month for harvesting Murcott (SSC/TA: 13.10 to 18.0) and Temple (SSC/TA:10.3 to 12.50). Sensory perception of sweetness, ripeness, and juiciness increased as SSC/TA increased while sourness and bitterness decreased. Pumpkin flavor, an indicator of overripe fruit, was mainly noticed late in the season. Tangerine flavor tended to decrease, whereas fruity‐noncitrus flavor tended to increase with fruit maturity. Monoterpenes were the most abundant volatiles and tended to decrease with fruit maturity, whereas alcohols, esters, and aldehydes increase. Aldehydes, esters, and alcohols were positively correlated with sweetness, ripeness, juiciness, and fruity characteristics, and negatively with sourness and bitterness. On the other hand, monoterpenes were positively correlated with bitterness and tangerine flavor, and negatively correlated with sweetness and fruity‐noncitrus flavor. The highest number of esters was found in Temple, whereas Murcott and 411 were high in aldehydes.